Northwestern Juvenile Project (Cook County, Illinois), Follow-up 3, 1999-2007 - Teplin, Linda A. ([Verlag nicht ermittelbar], 2017)
This study contains data from the third follow-up interview of the Northwestern Juvenile Project (NJP), a longitudinal assessment of alcohol, drug, or mental service treatment needs of juvenile detainees. The third follow-up occurred approximately four years after the baseline interview and focused on studying the development and persistence of psychiatric disorders, related predictive variables, patterns of drug use, and other risk behaviors. The project's aims included studying (1) development and persistence of alcohol, drug, and mental disorders and (2) pathways and patterns of risky behaviors. Changes in disorders over time were studied (including onset, remission, and recurrence), comorbidity, associated functional impairments, and the risk and protective factors related to these disorders and impairments. This study addressed patterns and sequences of the development of drug use and related variables, focusing on gender differences, racial/ethnic differences, the antecedents of these risky behaviors (risk and protective factors), and how these behaviors were interrelated. The original sample included 1829 randomly selected youth, 1172 males and 657 females, then 10 to 18 years old, enrolled in the study as they entered the Cook County Juvenile Temporary Detention Center from 1995 to 1998. Among the sample were 1005 African Americans, 524 Hispanics, 296 non-Hispanic white respondents. Participants were tracked from the time they left detention. A random subsample of 997 of the baseline participants were chosen for third follow-up interviews. Re-interviews were conducted regardless of where respondents were living when their follow-up interview was due: in the community, correctional settings, or by telephone if they lived farther than two hours from Chicago.